2012
DOI: 10.2478/s11756-012-0069-y
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Placobdella costata (Fr. Müller, 1846) (Hirudinida: Glossiphoniidae) and mud turtle Emys orbicularis

Abstract: Emys orbicularis is receding from Europe, mainly due to anthropogenic habitat changes. Its parasite, Placobdella costata, is widely distributed within both the former and the present distribution range of the host. Though closely associated with the mud turtle, it may have other hosts (birds, amphibians, reptiles). Its reproductive period coincides with that of its host's migration to the breeding grounds, thus facilitating dispersal of the parasite. Based on literature data we have analyzed the geographic spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 9 publications
3
40
0
Order By: Relevance
“…Consistency between the results obtained by blood smear microscopy and PCR in the current study suggests the same sensitivity of both applied diagnostic methods, as it was previously reported in the study of Dvořáková et al (2014) [12]. Bielecki et al (2012) [28] observed the close association of Placobdella costata (the leech species vectoring H. stepanowi) and E. orbicularis, with intensity of leech invasion being related to the host size and body weight. Although no leeches were found infesting turtles in our study, high prevalence of H. stepanowi infection in intermediate hosts indicates the presence of the leech vector at the same collection site.…”
Section: Discussionsupporting
confidence: 90%
“…Consistency between the results obtained by blood smear microscopy and PCR in the current study suggests the same sensitivity of both applied diagnostic methods, as it was previously reported in the study of Dvořáková et al (2014) [12]. Bielecki et al (2012) [28] observed the close association of Placobdella costata (the leech species vectoring H. stepanowi) and E. orbicularis, with intensity of leech invasion being related to the host size and body weight. Although no leeches were found infesting turtles in our study, high prevalence of H. stepanowi infection in intermediate hosts indicates the presence of the leech vector at the same collection site.…”
Section: Discussionsupporting
confidence: 90%
“…(see Marrone et al 2016a). Such an unexpected decoupling might be due to a recent, human-mediated introduction of the leech to Sicily, which would be also supported by the evidence of the presence of introduced specimens of E. orbicularis from Italy in Lago Urio Quattrocchi (Vamberger et al 2015), or to a natural long-range passive dispersal event of the species, which is reported to be able to be dispersed by non-chelonian vertebrates with aquatic afinity (Vamberger and Trontelj 2007, Bielecki et al 2012, Marrone et al 2016a.…”
Section: Discussionmentioning
confidence: 78%
“…It occurs from the Iberian Peninsula to the Balkan Peninsula and the Black Sea coast (Bielecki et al 2012). It is also ranges from Morocco to Iran and the northern Caucasus (Saglam 2001).…”
Section: Introductionmentioning
confidence: 99%
“…costata reproduces in summer (Sawyer 1986) although its life cycle has not been studied completely. The species displays parental care, another characteristic feature of specialists (Bielecki et al 2012). Individuals take care of embryos or young outside the hosts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation